Effects of aeration, agitation and pH on the production of mycelial biomass and exopolysaccharide from the filamentous fungus Ganoderma lucidum1 (2017)
Due to the increasing demand for functional foods and dietary supplements, mushroom production has increased significantly in recent years, which is why the study of operational conditions affecting the biotechnology cultivation of these mushrooms has become the aim of numerous studies. This study attempted to know the effect of pH, agitation and aeration on the biomass and polysaccharides production of filamentous fungus Ganoderma lucidum in fermentations made in a 5L bioreactor. The results allowed to establish that a bistage pH strategy (one stage with a fixed pH control, and a second stage without control), combined with hydrodynamic stress, which involves high agitation and high aeration, favors biomass and polysaccharides production, achieving increases of up to 100% compared to that obtained with the reference conditions.